Towards an Understanding of the Anti-Aging Mechanism of Caloric Restriction - Cavallini, Gabriella; Donati, Alessio; Gori, Zina; Bergamini, Ettore (Current Aging Science, 2008)
Accumulation of oxidatively altered cell components may play a role in the age-related cell deterioration and associated diseases. Caloric restriction is the most robust anti-aging intervention that extends lifespan and retards the appearance of age-associated diseases. Autophagy is a highly conserved cell-repair process in which the cytoplasm, including excess or aberrant organelles, is sequestered into double-membrane vesicles and delivered to the degradative vacuoles. Autophagy has an essential role in adaptation to fasting and changing environmental conditions. Several pieces of evidence show that autophagy may be an essential part in the anti-aging mechanism of caloric restriction: 1. The function of autophagy declines with increasing age; 2. The temporal pattern of the decline parallels the changes in biomarkers of membrane aging and in amino acid and hormone signalling. 3. These age-dependent changes in autophagy are prevented by calorie restriction. 4. The prevention of the changes in autophagy and biomarkers of aging co-varies with the effects of calorie restriction on life-span. 5. A long-lasting inhibition of autophagy accelerates the process of aging. 6. A long-lasting stimulation of autophagy retards the process of aging in rats. 7. Stimulation of autophagy may rescue older cells from accumulation of altered mtDNA. 8. Stimulation of autophagy counteracts the age-related hypercholesterolemia in rodents. It is suggested that the pharmacological intensification of suppression of aging (P.I.S.A. treatment) by the stimulation of autophagy might prove to be a big step towards retardation of aging and prevention of age-associated diseases in humans.
Keywords: Aging